2013
DOI: 10.1098/rsbl.2013.0530
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of sperm damage in Chernobyl passerine birds suggest a trade-off between sperm length and integrity

Abstract: Interspecific variation in sperm size is enigmatic, but generally assumed to reflect species-specific trade-offs in selection pressures. Among passerine birds, sperm length varies sevenfold, and sperm competition risk seems to drive the evolution of longer sperm. However, little is known about factors favouring short sperm or constraining the evolution of longer sperm. Here, we report a comparative analysis of sperm head abnormalities among 11 species of passerine bird in Chernobyl, presumably resulting from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…They also found that abnormality rates were correlated with reduced levels of antioxidants in the blood, liver, and eggs of these birds, supporting the hypothesis that antioxidants likely play a significant role in protecting DNA from the direct and indirect consequences of exposure to radionuclides. And a more recent analysis of Chernobyl birds found that in 9 out of 10 species examined, sperm abnormality rates were much larger for birds living in Chernobyl than those living in control areas across Europe, with the highest damage levels observed for species with longer sperm (Hermosell et al 2013), suggesting that sperm abnormalities are likely common for birds living in radioactive areas. Sperm behavior is also negatively affected by radiation exposure history .…”
mentioning
confidence: 99%
“…They also found that abnormality rates were correlated with reduced levels of antioxidants in the blood, liver, and eggs of these birds, supporting the hypothesis that antioxidants likely play a significant role in protecting DNA from the direct and indirect consequences of exposure to radionuclides. And a more recent analysis of Chernobyl birds found that in 9 out of 10 species examined, sperm abnormality rates were much larger for birds living in Chernobyl than those living in control areas across Europe, with the highest damage levels observed for species with longer sperm (Hermosell et al 2013), suggesting that sperm abnormalities are likely common for birds living in radioactive areas. Sperm behavior is also negatively affected by radiation exposure history .…”
mentioning
confidence: 99%
“…For the Passeriformes, sinistrality has previously also been reported in, for example, Hirundo rustica Linnaeus, 1758, Turdus merula Linnaeus, 1758, Fringilla coelebs Linnaeus 1758, Sturnus vulgaris Linnaeus, 1758, and Poephila acuticauda (Gould, 1839 (Retzius, 1909;Vernon and Woolley, 1999;Hermosell et al, 2013;Rowe et al, 2015).…”
Section: Discussionmentioning
confidence: 70%
“…As such, investigating further adverse effects from supplementary feeding on this species is particularly important, as it could help inform potential conservation actions and ensure that provided foods improve the situation of urban greenfinches rather than contributing to further decline. Finally, we have in the past observed remarkably high rates of abnormal sperm in the greenfinch, especially in when several samples showed around 50% sperm abnormalities (n = 13, mean: 35.23%, range: 0–60%), as well as indications of elevated rates of abnormal sperm in the hawfinch (Hermosell et al ). These observations motivated the collection of more extensive sampling for the current study.…”
Section: Methodsmentioning
confidence: 85%
“…abnormal sperm in the greenfinch, especially in 2013 when several samples showed around 50% sperm abnormalities (n = 13, mean: 35.23%, range: 0-60%), as well as indications of elevated rates of abnormal sperm in the hawfinch (Hermosell et al 2013). These observations motivated the collection of more extensive sampling for the current study.…”
Section: Study Speciesmentioning
confidence: 94%